Cognitive workload across the spectrum of cognitive impairments: A systematic review of physiological measures. (September 2017) - Ranchet, Maud; Morgan, John C.; Akinwuntan, Abiodun E.; Devos, Hannes
Highlights: Cognitive workload is defined as the mental effort required to execute a task. Greater cognitive workload was found in healthy older adults compared to younger adults. The same was observed in patients with mild cognitive impairment compared to healthy older adults. Behavioral performance declined when cognitive resources available became insufficient. Potential of physiological measures in early detection of cognitive deficits. Abstract: Our objective was to identify the physiological measures that are sensitive to assessing cognitive workload across the spectrum of cognitive impairments. Three database searches were conducted: PubMed, PsychINFO, and Web of Science. Studies from the last decade that used physiological measures of cognitive workload in older adults (mean age >65 years-old) were reviewed. The cognitive workload of healthy older individuals was compared with the cognitive workload of younger adults, patients with mild cognitive impairment (MCI), and patients with Alzheimer's diseases (AD). The most common measures of cognitive workload included: electroencephalography, magnetoencephalography, functional magnetic resonance imaging, pupillometry, and heart rate variability. These physiological measures consistently showed greater cognitive workload in healthy older adults compared to younger adults when performing the same task. The same was observed in patients with MCI compared to healthy older adults. Behavioral performance declined when the available cognitive resources became insufficient to cope with the cognitive demands of a task, such as in AD. These findings may have implications for clinical practice and future cognitive interventions.